Two distinct Xenopus genes with homology to MyoD1 are expressed before somite formation in early embryogenesis. - Scales, J B (1990)
The myogenic factors MyoD1 and myogenin contain a conserved region with similarity to the myc family of proto-oncogenes. To identify amphibian genes structurally and functionally related to these myogenic factors, we screened a Xenopus laevis embryo cDNA library under conditions of reduced stringency with probes corresponding to the myc-like helix-loop-helix motif of mouse MyoD1 and myogenin. Several distinct cDNAs that are highly related to each other and share extensive homology to MyoD1 were isolated. Transcripts from two of these genes, Xlmf1 and Xlmf25 (X. laevis myogenic factor), reach maximal levels of accumulation during gastrulation, remain at constant levels through early embryogenesis, and are found exclusively in skeletal muscles of adult frogs. The appearance of these transcripts early in development precedes the expression of cardiac alpha-actin, a molecular marker for mesoderm formation. A third cDNA, Xlmf11, contains an internal 351-base-pair deletion downstream of the myc homology region and encodes a truncated version of the protein encoded by Xlmf1. When expressed in mouse pluripotential stem cells, Xlmf1 activates the muscle cell differentiation program, resulting in expression of endogenous MyoD1, myogenin, and myosin heavy-chain genes and formation of multinucleated myotubes.